THE INFLUENCE OF CAREER DEVELOPMENT AND COMPENSATION ON EMPLOYEE JOB SATISFACTION - Distria, Elka; Mariana, R Adjeng (LPPM STIE Muhammadiah Bandung, 2024)
This study aims to determine its impact on employee career development, compensation decisions, and job satisfaction. The data collection technique was carried out by distributing questionnaires with a sample of 132 respondents. The study showed that employees of PT BPR Kerta Raharja (Perseroda) have a high level of career development, compensation and job satisfaction. The results of the study indicate that the amount of remuneration of PT BPR Kelta Lalharja (Perseroda) can explain the difference in job satisfaction based on the results of hypothesis testing. Employee job satisfaction was assessed high in a descriptive statistical study using the SPSS 25 program and several linear regression tests. Career development and compensation have an effect on employee job satisfaction. Based on the test results, it is known that variations in career development and reward variables can explain differences in employee work, meaning that variations in career development and compensation variables are sufficient, then the work determines the conditions for career development that will also increase satisfaction. Compensation and job satisfaction of employees of PT. BPR Kerta Raharja (Perseroda) know the impact of career development and compensation on employee job satisfaction. Because the variables studied are interrelated, the method used is quantitative with a descriptive and confirmatory approach.